2015
DOI: 10.5217/ir.2015.13.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms inPRKCDBP, a Transcriptional Target of TNF-α, Are Associated With Inflammatory Bowel Disease in Korean

Abstract: Background/AimsEmerging data indicate that polymorphic sequence variations in the tumor necrosis factor alpha (TNF-α) gene may affect its production, and be associated with the risk of inflammatory bowel disease (IBD). PRKCDBP is a putative tumor suppressor gene and a transcriptional target of TNF-α. The aim of this case-control study is to explore the possible association of single nucleotide polymorphisms (SNPs) in PRKCDBP with the development of IBD in Koreans.MethodsGenotyping analysis of four SNPs of PRKC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…We compared the PRKCDBP OE A549/DDP group and the PRKCDBP NC A549/DDP group by mRNA expression profiling, and it was found that TNF-α could regulate PRKCDBP. These results are consistent with some literature reports (17,20,21). TNF-α resulted in an increase of the PRKCDBP mRNA level, while TNF-α siRNA led to a decrease thereof (P<0.001).…”
Section: Discussionsupporting
confidence: 93%
“…We compared the PRKCDBP OE A549/DDP group and the PRKCDBP NC A549/DDP group by mRNA expression profiling, and it was found that TNF-α could regulate PRKCDBP. These results are consistent with some literature reports (17,20,21). TNF-α resulted in an increase of the PRKCDBP mRNA level, while TNF-α siRNA led to a decrease thereof (P<0.001).…”
Section: Discussionsupporting
confidence: 93%
“…CDX1 promoter methylation was highly consistent with NF-κB signal activation, but inversely associated with TNF-α expression in the carcinogen-induced stomach cancer development 43 . TNF-α-induced hypermethylation of PRKCDBP was associated with NF-κB activation in the tumor suppressive effect of PRKCDBP in colorectal cancer 47 . TNF-β stimulation causes cadherin and collagen 1/g1 methylation by DNMT activation in the EMT and metastasis in ovarian cancer 48 .…”
Section: Discussionmentioning
confidence: 95%
“…A previous study found that CaMK1, a class of protein kinases, could regulate protein phosphorylation by binding to Ca (2+)/calmodulin, and the polymorphism in the calmodulin-dependent kinase isomer D (CaMK1D) gene was associated with the development of diabetes as well as improved insulin sensitivity and glycemic control in obese mouse model ( Fromont et al., 2020 ). The polymorphisms in the PRKCDBP gene can be used as a transcriptional target for TNF-α to cause intestinal inflammatory diseases ( Kim et al., 2015 ). In the current study, the interaction between the upregulation of CaMK1 and PRKCDBP genes and these microbes ( Mycoplasma_sp._CAG:472 , Clostridium_sp._CAG:793 , and Akkermansia glycaniphila ) in the cecum were also highly correlated in the correlation network, suggesting a key regulatory function of lipid metabolism and the immune response in the mucosal layer of the cecum.…”
Section: Discussionmentioning
confidence: 99%